1996
DOI: 10.1037/0278-6133.15.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Elevated physical health risk among gay men who conceal their homosexual identity.

Abstract: This study examined the incidence of infectious and neoplastic diseases among 222 HIVseronegative gay men who participated in the Natural History of AIDS Psychosocial Study. Those who concealed the expression of their homosexual identity experienced a significantly higher incidence of cancer (odds ratio = 3.18) and several infectious diseases (pneumonia, bronchitis, sinusitis, and tuberculosis; odds ratio = 2.91) over a 5-year follow-up period. These effects could not be attributed to differences in age, ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
216
1
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(233 citation statements)
references
References 35 publications
9
216
1
7
Order By: Relevance
“…Other work, in particular psychological research in the area of disclosure, has suggested that at least one more stress process is important: concealment of one's sexual orientation. Hiding of sexual orientation can be seen as a proximal stressor because its stress effect is thought to come about through internal psychological (including psychoneuroimmunological) processes (Cole, Kemeny, Taylor, & Visscher, 1996a, 1996bDiPlacido, 1998;Jourard, 1971;Pennebaker, 1995).Distal minority stressors can be defined as objective stressors in that they do not depend on an individual's perceptions or appraisals-although certainly their report depends on perception and attribution (Kobrynowicz & Branscombe, 1997;Operario & Fiske, 2001). As objective stressors, distal stressors can be seen as independent of personal identification with the assigned minority status (Diamond, 2000).…”
mentioning
confidence: 99%
“…Other work, in particular psychological research in the area of disclosure, has suggested that at least one more stress process is important: concealment of one's sexual orientation. Hiding of sexual orientation can be seen as a proximal stressor because its stress effect is thought to come about through internal psychological (including psychoneuroimmunological) processes (Cole, Kemeny, Taylor, & Visscher, 1996a, 1996bDiPlacido, 1998;Jourard, 1971;Pennebaker, 1995).Distal minority stressors can be defined as objective stressors in that they do not depend on an individual's perceptions or appraisals-although certainly their report depends on perception and attribution (Kobrynowicz & Branscombe, 1997;Operario & Fiske, 2001). As objective stressors, distal stressors can be seen as independent of personal identification with the assigned minority status (Diamond, 2000).…”
mentioning
confidence: 99%
“…The difficulties of being single and wanting to play the field but having performance issues are contrasted to the feelings of letting one's partner down or having one's partner have to deal with the complications of cancer (or any health challenge) in their relationship. Finally, as we have detailed about GLBTQ aging persons, gay men are more likely to have difficulty dealing with the medical community of mainly heterosexually oriented urologists and oncologists (Cole, Kemeny, Taylor, & Visscher, 1996;Gay and Lesbian Medical Association, 2001;Silvestre, 2001). Many providers may indeed be biased, by prejudice or sheer lack of knowledge or attention.…”
Section: T O Blank Et Almentioning
confidence: 99%
“…Assim, se pensarmos que a não identificação identitária está intimamente ligada a factores de inibição psicológica, pode-se adivinhar uma relação entre a mesma e resultados de saúde física e psicológica, dos quais a progressão em relação ao VIH e a sintomatologia psicossomática são apenas alguns exemplos (S. W. Cole, M. E. Kemeny, S. E. Taylor & B. R. Visscher, 1996).…”
unclassified